Financial Management Strategy for Micro, Small and Medium Enterprises Post-Pandemic: A Qualitative Approach Based on Interviews with MSME Actors - Saman, Saman (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study investigates the financial management mechanisms of micro, small and medium business entities in the context of the post-COVID-19 pandemic era that has catalyzed a fundamental metamorphosis in the financial governance of the sector. The objective of the research is to identify and analyze the strategic modifications developed by MSME practitioners in confronting economic challenges after the global health crisis. A qualitative methodology with a semi-structured comprehensive interview approach was implemented on 18 MSME practitioners from various sectors who experienced significant impacts during the pandemic period. The thematic analysis reveals five key dimensions of transformation: adaptation of systematic financial administration, implementation of digital technologies in financial management, structural and operational barriers, the role of external support, and long-term sustainability implications. The findings indicate that MSME practitioners have undergone a paradigmatic evolution from traditional financial management to a technology-integrated framework with digital documentation systems, business-individual account segregation, and proactive cash flow control. External interventions have proven to be effective when integrating financial assistance with technical mentoring. This research contributes to the development of MSME financial management literature by presenting a holistic perspective on adaptation strategies in dealing with economic uncertainty.